Perfusion MR Neuroimaging in Patients Undergoing Balloon Test Occlusion of the Internal Carotid Artery - Michel, Eduard; Liu, Haiying; Remley, Kent B.; Martin, Alastair J.; Madison, Michael T.; Kucharczyk, John; Truwit, Charles L. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: We sought to investigate whether the combination of conventional, diffusion-weighted, and perfusion-weighted MR imaging increases the diagnostic accuracy of balloon test occlusion of the internal carotid artery. We describe perfusion anomalies and patterns of enhancement seen in areas of altered brain perfusion during MR-monitored temporary balloon occlusion of the internal carotid artery.METHODS: Nine patients underwent balloon occlusion testing under standard angiographic conditions with continuous clinical and EEG monitoring. One patient who failed the test by clinical criteria underwent an external carotid to internal carotid bypass operation, followed by a repeat balloon test occlusion, thereby bringing the total number of procedures to 10. Patients were further imaged at 1.5 T with perfusion- and diffusion-weighted imaging as well as with conventional noncontrast and contrast-enhanced turbo fluid-attenuated inversion recovery (FLAIR) and T1-weighted sequences.RESULTS: Seven of 10 patients who tolerated unilateral carotid test occlusion without adverse clinical neurologic or EEG changes exhibited delayed first-pass transit of contrast material through the affected cerebral hemisphere, indicative of altered perfusion without significant concurrent cerebral blood flow or blood volume changes. Four of these patients and both symptomatic patients showed pial or subarachnoid contrast staining in areas of altered perfusion without abnormalities on diffusion-weighted images.CONCLUSION: Our findings indicate that MR perfusion-weighted imaging is safe and easily accomplished in a high-field-strength magnet and that contrast-enhanced turboFLAIR imaging may provide clinically useful MR imaging evidence of abnormal cerebral blood flow and subclinical ischemia.